Scientometric analysis of lipid metabolism in macrophage polarization: 2013-2023 - Ye, Chenxiao; Ru, Xiaosong; Guo, Yong (Frontiers in Oncology, 2025)
IntroductionMacrophage polarization plays a crucial role in the development of various diseases. Simultaneously, macrophage polarization is intimately related to lipid metabolism. To assess the emerging trend of lipid metabolism during macrophage polarization, the present study was carried out.MethodsFirst, 472 publications that explored lipid metabolism during macrophage polarization were gathered using the Web of Science Core Collection database (WoSCC). The emerging trends were then described using CiteSpace.ResultsBetween 2013 and 2023, 46 countries/regions involving 268 institutions carried out studies in this field. The largest number of publications was found in China. Additionally, the most recent burst keywords included “immunometabolism”, “foam cell formation”, and “pathway”, which represented the current frontiers of research.DiscussionThe detailed analysis of publications pertaining to lipid metabolism during macrophage polarization reveals the current research status and identifies its hotspots.